2014
DOI: 10.1007/s10597-014-9761-4
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Service Users’ Information Needs and Preferences When Receiving a Serious Mental Health Diagnosis

Abstract: Helpful strategies for communicating news of a serious mental health diagnosis are poorly understood. This study explored service users' preferences for how they would like clinicians to deliver such news when a diagnosis of mental illness is made. Qualitative interviews were conducted with forty-five individuals identifying with serious mental illness in eleven community based mental health facilities. Inductive thematic analysis resulted in eight primary themes. Five themes related to the structure and conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…(p.1227) 64 I knew what was wrong with me, and if I knew what was wrong with me I had a chance of possibly understanding it better and maybe work on it a bit more… (p.461) 76 Because some people just think borderline personality means difficult patient you know and I, that's not my opinion, but the thing is because of all that bad press of borderline um I don't bring that up right away. (p.87) 86 Open diagnostic information sharing was often recommended by participants as it provided an understanding of the issues and symptoms, and facilitated access to treatment and support… (p.461) 76 It was a matter of concern that several people reported they had only discovered their diagnosis by accident, for example, on the back of a Disability Living Allowance form, on a hospital discharge certificate and, in one case unfortunately, on receiving a letter from their consultant asking if they would like to take part in this research… Apart from the shock of finding out such sensitive information in this way, the lack of any accompanying explanation left these individuals feeling anxious and upset. (pp.363-4) 7…”
Section: Acknowlegementsmentioning
confidence: 99%
See 3 more Smart Citations
“…(p.1227) 64 I knew what was wrong with me, and if I knew what was wrong with me I had a chance of possibly understanding it better and maybe work on it a bit more… (p.461) 76 Because some people just think borderline personality means difficult patient you know and I, that's not my opinion, but the thing is because of all that bad press of borderline um I don't bring that up right away. (p.87) 86 Open diagnostic information sharing was often recommended by participants as it provided an understanding of the issues and symptoms, and facilitated access to treatment and support… (p.461) 76 It was a matter of concern that several people reported they had only discovered their diagnosis by accident, for example, on the back of a Disability Living Allowance form, on a hospital discharge certificate and, in one case unfortunately, on receiving a letter from their consultant asking if they would like to take part in this research… Apart from the shock of finding out such sensitive information in this way, the lack of any accompanying explanation left these individuals feeling anxious and upset. (pp.363-4) 7…”
Section: Acknowlegementsmentioning
confidence: 99%
“…(p.53) 5 I can't emphasise this enough… I would have accepted it more if they explained what schizophrenia was… (p.731) 3 Individuals indicated that diagnostic conversations that were devoid of hope were extremely immobilizing and potentially dangerous…hope-focused discussions centered on recognition that individuals could live meaningful lives and be productive members of society. (p.462) 76 Where diagnosis was disclosed, sometimes the lack of information that accompanied that disclosure was one of the main causes of disempowerment. Lack of information meant participants often experienced diagnosis as 'a prognosis of doom' about their future.…”
Section: Provision Of Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiences of mental health services have been studied from the perspectives of consumers with various mental illnesses and their carers. Consumers describe the importance of mental health professionals discussing diagnoses with consumers and carers, and providing hope and information regarding diagnosis [15]. Regarding treatment planning, consumers want to be involved in their treatment decisions [16], although they are often excluded from participating in decision making [17].…”
Section: Introductionmentioning
confidence: 99%